SPEAKING SKILL DEVELOPMENT FOR VOCATIONAL HIGH SCHOOL STUDENTS USING GROUP DISCUSSION - Sukmawati Sukmawati; Sukmawati Yasim; Nurul Imansari (Tekstual, 2023)
This study aims to determine the improvement of student speaking in discussions in 11th grade students of SMA 2 Majene in the 2022 academic year. The research method applied is experimental research (quantitative method). The subjects of this study were the 11th grade students of SMKN 2 majene with a total of 40 people. The sampling technique employ the random sampling method. The instruments used in this study were tests and questionnaires. The type of test for speaking is an oral test, the researchesr give a picture in class and then students are asked to describe the picture. From the research data, it was found that the students' t-test scores (-4.171) from df (19). Based on the output it was obtained value of Sig. (2-tailed) 0.001 0.05, then it can be concluded there is a difference in students' outcomes between in pre-test and post-test.Ã‚Â In conclusion,Ã‚Â implementing group discussion learning to teach speaking is effective to improve vocational high school studentsÃ¢â‚¬â„¢ speaking proficiency.Keywords:Ã‚Â Speaking Proficiency, Group Discussion, Vocational High School.Ã‚Â